Determination of Methylation Site of DNA-Methyltransferase NlaX by a Hybrid Method. (September 2002) - Kubareva, E.A.; Walter, J.; Karyagina, A.S.; Vorob'eva, O.V.; Lau, P.C.K.; Trautner, T.
Using a new method based on a combination of bisulfite reaction, the repair enzyme uracil-DNA glycosylase, and synthetic oligodeoxyribonucleotides, the methylation site of DNA-methyltransferase Nla X (M· Nla X) from Neisseria lactamica was established to be the inner cytosine in the double-stranded pentanucleotide recognition sequence 5′-CCNGG-3′ (where N = any nucleoside). 5-Methylcytosine (m 5 C) type modification by M· Nla X was confirmed by the use of oligonucleotide substrates that contain 5-fluoro-2′-deoxycytidine.